Chemistry of polyfunctional molecules. 114. Synthesis and structure of an ionic and nonionic cyclic carbaphosphazene and of a cobalt(III) phosphazene complex - Ellermann, J.; Sutter, Jörg; Knoch, Falk; Moll, Matthias; Bauer, Walter (Zeitschrift für Naturforschung Section B-A Journal of Chemical Sciences, 1994)
Reaction of Co(L-P,P)(L-N,P) (1; HL = Ph2PN:P(Ph2)N:(Ph2)PH) in CH2Cl2 with benzimidazole yields I.Cl. I.BPh4 was prepd. in THF by metathesis of I.Cl with NaBPh2. Deprotonation of the cationic ring in I.BPh4 was accomplished using 1,8-diazabicyclo[5.4.01,7]undec-7-ene and resulted in II. Treating 1 with 8-hydroxyquinoline (HQ) in CH2Cl2 yields the octahedral cis-CoQ2(L-P,P) (7). I.BPh4, II and 7 were characterized by their IR, Raman, 31P[1H] NMR, 13C[1H] NMR, 1H NMR and mass spectra. Crystals suitable for x-ray structure analyses were obtained for I.BPh4 and 7.0.5CH2Cl2. The colorless plates of I.BPh4 crystallize in the triclinic space group P̅1, with a 1172.7(3), b 1326.2(3), c 1806.1(6) pm; α 100.79(2), β 103.71(3), γ 108.18(2)°. The black blocks of 7.0.5CH2Cl2 crystallize in the monoclinic space group P21/c with a 1159.0(10), b 2008.9(10), c 2034.6(12) pm; β 105.86(5)°. [on SciFinder(R)]
Keywords: CYCLIC CARBAPHOSPHAZENE SYSTEMS; COBALT COMPLEXES; SYNTHESES; NMR SPECTRA; X-RAY